Immanenz & Einheit : Festschrift zum 70. Geburtstag von Rolf Kühn - Kühn, Rolf, 1944-; Enders, Markus (Studies on the interaction of art, thought and power., 2015)
Based on the philosophy of Michel Henry, the contributions of the anthology "Immanenz und Einheit" give different phenomenological and metaphysical foundations of the relation between immanence and unity, examine its perspectives for philosophy of religion and analyse its ethical consequences. Ausgehend vom Werk Michel Henrys geben die in der Festschrift "Immanenz und Einheit" gesammelten Beiträge phänomenologische und metaphysische Grundlegegungen für das Verhältnis zwischen Immanenz und Einheit und untersuchen die religionsphilosophischen Perspektiven und ethischen Konsequenzen, die sich aus.